Evaluation of a Home Visiting Program: Perspectives of Mothers. (March 2021) - Lowe, Kelsi; Cartagena, Diana; Gudger, Kaitlin
Abstract : Home visiting programs provide families with an array of services that contribute to decreased infant and maternal morbidity and mortality. However, little is known as to how mothers perceive participation in home visiting programs, and questions remain regarding what improvements can be made to better serve these families. The purpose of this program evaluation was to assess mothers' perceived benefits and barriers to participation in established home visiting and outreach programs at Child Developmental Resources (CDR) in Williamsburg, Virginia. The program evaluation was a descriptive project consisting of 30-minute telephone interviews. Participants included 23 English-speaking mothers enrolled in CDR programs. Maternal demographics and perception of benefits/barriers were measured. Descriptive statistics were performed to describe sample demographics and outcome variables. Overall, most mothers perceived CDR programs as beneficial and were very satisfied with the services; however, a few changes could be made to improve programs and combat barriers to participation. Potential alternatives to supplement programs were suggested including the use of mobile technology in the participant's home.